Characterization of von Karman street with seal whisker-like sensor - Hans, Hendrik (2013)
Harbor seals are known to track the hydrodynamic trails of their prey with only their whiskers. The geometry of their whiskers has been found to reduce vortex induced vibration (VIV). In this study, we develop an artificial whiskerlike sensor to evaluate the sensitivity and effectiveness of the seal whisker-like sensor configuration for underwater detection. These whisker-like sensors are towed downstream of a circular cylinder to determine their ability to characterize von Karman wakes. The results show that the seal whisker-like models are four times as sensitive as circular cylinder model in detecting the von Karman street wakes. The whisker-like models are also found to vibrate at the frequency of the generated wakes. These results indicate that the seal whisker-like sensor is very suitable for underwater detection.